2023
DOI: 10.1029/2022gl101294
|View full text |Cite
|
Sign up to set email alerts
|

Declines in Peak Snow Water Equivalent and Elevated Snowmelt Rates Following the 2020 Cameron Peak Wildfire in Northern Colorado

Abstract: Wildfire activity increased markedly in the western United States beginning in the 1980s (Iglesias et al., 2022;Westerling, 2016) as a result of increased fuel loads due to a history of fire suppression, natural climate variability, and anthropogenic-driven climate change (Abatzoglou & Williams, 2016). Elevations exceeding 2,500 m saw the largest increase in burned area between 1984and 2017(Alizadeh et al., 2021, calling attention to the pronounced shift of wildfires from the intermittent snow zone and into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Independent of the reason for a later snow-free date, the result is still an increase in LSA over a longer period relative to nearby unburned areas. Previous research has shown that snow ablates earlier in burned areas compared to control unburned areas (Gleason et al, 2013;Kampf et al, 2022;McGrath et al, 2023) in studies using field observations and MOD10A1 SCF to determine a melt-out date. Our results largely agree with these results, but we argue snow depletion date alone does not tell the whole story.…”
Section: Discussionmentioning
confidence: 99%
“…Independent of the reason for a later snow-free date, the result is still an increase in LSA over a longer period relative to nearby unburned areas. Previous research has shown that snow ablates earlier in burned areas compared to control unburned areas (Gleason et al, 2013;Kampf et al, 2022;McGrath et al, 2023) in studies using field observations and MOD10A1 SCF to determine a melt-out date. Our results largely agree with these results, but we argue snow depletion date alone does not tell the whole story.…”
Section: Discussionmentioning
confidence: 99%
“…Climate warming threatens snow–water storage through feedbacks between declining snowpacks and increased forest fire activity (Fassnacht & López‐Moreno, 2020; Gleason et al, 2019; Kampf et al, 2022; McGrath et al, 2023; Viviroli et al, 2007). The majority of water in the American West is seasonally stored in snowpack, with ecosystems and human communities relying on snowmelt as a source of water in the drier periods of late spring and summer (Li et al, 2017; Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The overall net change in combined net shortwave and longwave radiative forcing on snowpack following canopy removal depends on the forest structure and snow climate (Lundquist et al, 2013; Musselman et al, 2008; Varhola et al, 2010). In addition to the enhanced radiation effects, forest canopy removal may also increase the turbulent fluxes at the snow surface ultimately reducing snow–water storage and increasing snow melt rates (Harpold et al, 2014; McGrath et al, 2023).…”
Section: Introductionmentioning
confidence: 99%